Anatomia do nervo isquiático em ovinos da raça morada nova aplicada a clínica de pequenos ruminantes - Sousa, Êlika Suzianny de (2008)
In the last years have been increasing the interest for farms of goats and sheep within Brazil, furthermore is verified that are rare the citations in the referring literature for the origin and distribution of the sciatic nerve into musculature in small ruminant. Thus, the aim of this work was to promoter a detailed study regarding morphology neural of the sciatic nerve, which is of great importance for clinical conduct in small ruminant, contributing to prevent lesions of order iatrogenesis as through applications of medicines intramuscular and or for surgical procedures accomplished in the pelvic member. The experiment was executed in the Laboratory of Anatomy of the Rural Federal University of the Semi-arid. 20 stockings left carcasses of sheep were used, males of the Morada Nova race, with age between 6 and 7 months coming from Experimental farm of the EMPARN-RN. Thus, were proceeded dissections of the carcasses for exhibition of the ischiatic nerve, which the pieces has been conserved in freezer until the conclusion of the dissections. Simultaneously was placed on this cotton soaked in hydrogen peroxide to 20 volumes, staying for 12 followed hours for your clarification process, facilitating your visualization. It was verified variations in the number of lumbar vertebras and sacral of the sheep, which 90% of the animals presented 7 vertebras and 3 sacral and 10% had 6 lumbar vertebras and 4 sacral, altering consequently the origin of the nerve in these animals. In 15 animals (75%), the nerve were originated from L7S1S2; in two (10%), from L6S1S2; in two (10%) with L7S1S2S3 and in just one goat (5%), the formation of the nerve was originating from ventral branches of S1S2S3. In relationship the distribution of the ischiatic nerve for musculature, was observed in the muscle gluteobiceps innervations a variation from 2 to 5 branches; in semitendinosus muscle, sent among 1 to 3 branches; for quadriceps muscle of the thigh this contribution altered between 1 and 2 branches, which not was present in fifteen animals (75%); for the semimembranosus muscle, emitted between 2 and 4 threads. The sciatic nerve was found originating from the ventral branches of the sixth and seventh lumbar spinal nerves and of the first, second and third nerves spinal sacral